Factors Associated with Loss to Follow-Up (LtFU) among People Living with HIV/AIDS - Dian Widyahandayani; Ayun Sriatmi; Antono Suryoputro (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Loss to follow-up (LtFU) among people living with HIV/AIDS (PLWHA) receiving antiretroviral (ARV) therapy remains a significant challenge, contributing to treatment failure, drug resistance, and ongoing HIV transmission. This study aimed to identify factors associated with LtFU among PLWHA on ARV therapy in Demak Regency. Method: A quantitative observational analytic study with a cross-sectional design was conducted among 199 PLWHA meeting inclusion criteria. Data were collected using validated questionnaires addressing knowledge, attitudes, perceptions, family support, peer support, stigma, healthcare worker support, quality of health services, access to services, and health service policies. Data were analyzed using SPSS with univariate analysis, bivariate chi-square tests, and multivariate logistic regression at a 0.05 significance level with 95% confidence intervals (CI). Results in bivariate analysis indicated that all independent variables were significantly associated with LtFU (p < 0.05). Multivariate analysis identified six independent predictors: poor knowledge (OR = 4.68; 95% CI: 1.57–13.94), negative attitude (OR = 5.65; 95% CI: 1.98–16.08), poor perception (OR = 4.95; 95% CI: 1.69–14.45), inadequate family support (OR = 14.40; 95% CI: 3.75–55.37), poor service quality (OR = 4.40; 95% CI: 1.54–12.62), and a weak health service system reflecting limited access and provider support (OR = 5.61; 95% CI: 1.79–17.57). Collectively, these factors explained 72.65% of the variation in LtFU. In conclusion, LtFU is driven by a combination of cognitive, psychosocial, and structural determinants, with family support and health system factors being the most influential. Effective interventions should prioritize enhancing family involvement, patient education, and counselling, as well as improving service accessibility, quality, and responsiveness to ensure sustained retention in HIV care. Keywords: Antiretroviral, HIV/AIDS, Loss to Follow-Up, Risk Factors.